New templates for porphyrin nanorings - Liu, P (2016)
New templates based on the structures of cyclodextrin and ferrocene have been developed for porphyrin nanoring syntheses. Flexibility can be taken into account of the molecular template design. The flexibility of butadiyne bonds allow the formation of a 5-porphyrin nanoring, which is the smallest fully-conjugated porphyrin nanoring to date. Chapter 1 describes the general information of porphyrin, cyclodextrin and ferrocene, which are used as basic structures in the thesis. The polymer chemistry of porphyrins is reviewed as the background knowledge of the work. Meanwhile, chelate cooperativity of supramolecular systems and the corresponding measurement method are introduced. Chapter 2 presents the chemistry towards 6- and 7-porphyrin nanorings using molecular templates T6* and T7*, which are based on the α- and β-cyclodextrin scaffolds. The cooperativity of respective template-nanoring complexes was investigated by UV-vis titrations. Chapter 3 describes the Vernier-templated syntheses of porphyrin nanorings using T7* and different linear porphyrin oligomers (l-P2, l-P4 and l-P8). Both chapters focus on the influences of spatial preorganization and flexibility to the cooperativity of supramolecular systems. Chapter 4 introduces the chemistry towards a ferrocene-based five-dentate template T5 which successfully directed the syntheses of 5-porphyrin nanorings. Investigation of the cooperativity in the nanoring-template system is presented. Chapter 5 investigates the cooperativity between T5 and linear porphyrin oligomers in detail; and focuses on the contribution of partially-bound complexes in the measurement of equilibrium constants of the host-guest systems. Both chapters focus on the influences of intramolecular strain to the cooperativity in supramolecular systems. Chapter 6 provides experimental procedures and characterization data of the known and novel compounds synthesized in the course of completing the thesis.